Artificial Intelligence Adoption and Implementation In Indonesia: Policy Frameworks, Sectoral Applications, and Future Prospects - Saskiya Farannisa (RAM PUBLISHER, 2026)
Indonesia stands at a pivotal moment in its digital transformation journey, with Artificial Intelligence (AI) emerging as a strategic catalyst for economic growth and social development. This paper presents a comprehensive analysis of AI adoption and implementation in Indonesia, examining the national policy framework, sectoral applications, technological infrastructure, and institutional mechanisms established to accelerate AI development. The research reveals that Indonesia's National AI Strategy (Stranas KA) 2020-2045, complemented by institutional structures such as the AI Innovation Center (PIKA) and the Artificial Intelligence Industry Research and Innovation Collaboration (KORIKA), has created a comprehensive ecosystem for AI advancement. Current implementations span critical sectors including healthcare, agriculture, finance, manufacturing, and government services. However, significant challenges persist, particularly in digital infrastructure development, cybersecurity readiness, talent acquisition and retention, and ethical AI governance. Analysis of 43 recent studies from accredited journals indicates that quantitative research methodologies dominate AI investigations in Indonesia, with healthcare and education emerging as primary research foci. This paper concludes that while Indonesia possesses considerable potential to leverage AI for competitive advantage—with projected economic contributions reaching USD 366 billion over the next decade—successful realization requires sustained investment in infrastructure, comprehensive talent development programs, robust ethical frameworks, and enhanced cross-sector collaboration. The findings underscore the necessity of bridging the gap between policy formulation and operational implementation to ensure Indonesia emerges as a regional AI leader in Southeast Asia.